Integrating Reading as Evidence to Enhance Argumentation in Scientific Reading-based Inquiry: A Design-based Research in Biology Classroom - Probosari, R. M.; Sajidan, S.; Suranto, S.; Prayitno, B. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aims to design a Scientific Reading-based Inquiry (SRbI) model that supports argumentation skills development. The assessment of these skills refers to the Toulmin Argument Pattern (TAP), and the participants were Biology Education students in a state university. Furthermore, the Design-based Research (DBR) approach was adopted by combining exploratory studies, trials, and case studies as part of an iterative process. The intervention was formed based on design principles derived from literature review and findings from exploratory studies. Also, observations were made during the trial and intervention process. Data in assessments and observations of written and oral arguments were collected and descriptively analyzed. The study, in three iterations, produced a framework as the basis for the SRbI learning model, with five phases: Reading Orientation, Recapturing, Processing, Communicating, and Reviewing. Therefore, the application of this learning model had a significant impact on the development of students’ argumentation skills.